Heat load calculation and analysis for commercial building air conditioning system - Tan, Foo Chuan, author (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Thesis (Sarjana Kejuruteraan (Mekanikal)) - Universiti Teknologi Malaysia, 2017